Formulation and in vivo Evaluation of a Self-Microemulsifying Drug Delivery System of Dutasteride - Choo, G.-H.; Park, S.-J.; Hwang, S.-J.; Kim, M.-S. (Drug Research, 2013)
This study aimed to develop an effective formulation to improve the solubility and oral absorption of dutasteride by using a self-microemulsifying drug delivery system (SMEDDS). We used the d-optimal mixture design as a tool for developing an optimized SMEDDS formulation with excellent physicochemical characteristics such as mean particle size of <100 nm and percentage of drug dissolved at 15 min, >80%. An optimized dutasteride-loaded SMEDDS formulation consisted of 39.80% CapryolTM 90, 25.90% Cremophor® EL, and 34.30% Transcutol® HP and showed an emulsion droplet size of about 35.3 nm. Approximately 90% of dutasteride from the SMEDDS dissolved at 10 min in dissolution media of pH 1.2 and 6.8. Furthermore, pharmacokinetic studies in rats indicated that compared to the raw drug, the optimized SMEDDS formulation significantly improved the oral absorption of dutasteride. Therefore, preliminary results from our study suggest that the dutasteride-loaded self-microemulsifying formulation has a great potential for clinical application.
Keywords: dutasteride; self-microemulsifying drug delivery system; bioavailability; pharmacokinetics